Tailoring Noble Metal-Free Ti@TiO2 Photocatalyst for Boosting Photothermal Hydrogen Production - El Hakim, Sara; Chave, Tony; Nada, Amr A.; Roualdes, Stéphanie; Nikitenko, Sergey I. (Frontiers in Catalysis, 2021)
In this work, we provide new insights into the design of Ti@TiO2 photocatalyst with enhanced photothermal activity in the process of glycerol reforming. Ti@TiO2 nanoparticles have been obtained by sonohydrothermal treatment of titanium metal nanoparticles in pure water. Variation of sonohydrothermal temperature allows controlling nanocrystalline TiO2 shell on Ti0 surface. At 100